A feasible route to produce 1.1 GPa ferritic-based low-Mn lightweight steels with ductility of 47%. (1st August 2022) - Ko, Kwang Kyu; Bae, Hyo Ju; Park, Eun Hye; Jeong, Hyeon-Uk; Park, Hyoung Seok; Jeong, Jae Seok; Kim, Jung Gi; Sung, Hyokyung; Park, Nokeun; Seol, Jae Bok
Highlights: We describe a feasible method of avoiding the strength–ductility dilemma of typical ferrite-based lightweight steels by applying low-temperature tempering-induced partitioning (LTP) treatment. We show that the simultaneous increments of strength and total elongation of widely known low-Mn lightweight steel with a composition of Fe–2.8Mn–5.7Al–0.3C by wt.%, were achieved by strength of 1, 118 MPa and total elongation of 47%, through the facile route of LTP treatment. This size-dependent partitioning results in slip plane spacing modification and resultant lattice strain, which can act through dislocation engineering. The additional ductility and strengths, which result from the small austenite grains, is attributed to the easy passage of dislocations along slip planes (upon the early deformation), interface shielding effect of C-dislocations, delayed TRIP effect, and the cross-slip motions of mobile dislocations (at the high strain level). This size-dependent dislocation activity in austenite grains, as proposed here by LTP, offers a low raw-materials cost than that of high-Ni maraging steels as well as a low thermomechanical-processing cost than that of high-Mn TWIP steels, while maintaining an analogous strength–ductility balance for light weighting approach. Abstract: High- and medium-Mn (H/M-Mn) base lightweight steels are a class of ultrastrong structural materials with high ductility compared to their low-Mn counterparts with low strength and poor ductility. However, producing these H/M-Mn materials requires the advanced or high-tech manufacturing techniques, which can unavoidably provoke labor and cost concerns. Herein, we have developed a facile strategy that circumvents the strength–ductility trade-off in low-Mn ferritic lightweight steels, by employing low-temperature tempering-induced partitioning (LTP). This LTP treatment affords a typical Fe-2.8Mn-5.7Al-0.3C (wt.%) steel with a heterogeneous size-distribution of metastable austenite embedded in a ferrite matrix for partitioning more carbon into smaller austenite grains than into the larger austenite ones. This size-dependent partitioning results in slip plane spacing modification and lattice strain, which act through dislocation engineering. We ascribe the simultaneous improvement in strength and total elongation to both the size-dependent dislocation movement in austenite grains and the controlled deformation-induced martensitic transformation. The low-carbon-partitioned large austenite grains increase the strength and ductility as a consequence of the combined martensitic transformation and high dislocation density-induced hardening and by interface strengthening. Additionally, high-carbon-partitioned small austenite grains enhance the strength and ductility by planar dislocation glide (in the low strain regime) and by cross-slipping and delayed martensitic transformation (in the high strain regime). The concept of size-dependent dislocation engineering may provide different pathways for developing a wide range of heterogeneous-structured low-Mn lightweight steels, suggesting that LTP may be desirable for broad industrial applications at an economic cost.